Correlation between microstructures and mechanical properties in Ni-rich Ni–Mn–Ga high-temperature shape-memory alloys. Issue 6 (13th April 2018) - Hou, Long; Tong, Hui; Dai, Yanchao; Fautrelle, Yves; Moreau, Rene; Ren, Zhongming; Li, Xi
ABSTRACT: Microstructures and mechanical properties of polycrystalline and single-crystalline Ni55+ x Mn25 Ga20− x ( x = 1, 2, 3) alloys are investigated. The alloys exhibit a single martensite phase for x = 1, and two phases containing tetragonal martensite phase and face-centered γ phase for x = 2 and 3. The appearance of γ phase can apparently raise the strength and plasticity of the alloys. Moreover, single crystals show better mechanical properties compared with the polycrystals with the same composition. Furthermore, a kind of net-like γ phase is observed in directionally solidified Ni58 Mn25 Ga17 single crystal. This alloy exhibits excellent plasticity due to that the crack propagation is seriously hindered by the plastic net-like γ phase.